La NIC 38 y su Adopción en el Sector Manufacturero parque industrial Ambato, periodo 2018. - Escobar Chicaiza, Nelly Fernanda (2023)
The present research work studies "NIC 38 and its adoption in the Ambato industrial park manufacturing sector, period 2018", the purpose of being able to evaluate the incidence, in the entities of this sector. In the project, taking into account factors that provided and allowed to gather information to achieve it, a synthetic analytical research method is applied, also including a field and documentary research, with a quantitative approach and logically with a descriptive level. The information gathering technique was the surveys, which have been applied to the accountants of the 18 manufacturing companies of the Ambato industrial park, seeking to know with a practical example that allowed analyzing whether the adoption of IAS 38 was favorable to them. In addition, to know if there was an impact on its valuation and, to propose a methodology for recording the year 2018 in its intangible assets.